Evaluation of the aerobic capacity in swimming: Comparison among different methods in a case study - Pelarigo, J. G.; Pimenta, R. A.; Leao, H. F. P.; Júnior, M. A. H. S.; Filho, E. A. R.; Silva, T. C. A.; da Silva, P. M. A.; Denadai, B. S.; Fernandes, R. J.; Greco, C. C.; Vilas-Boas, J. P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In recent decades, one of the most debated topics in sport sciences has been the anaerobic threshold (AnT), with several researchers using different methods (and concepts) to find the intensity associated to the maximal aerobic pace , defined as the highest intensity of exercise that can be maintained without continuous accumulation of lactate along the time (Heck et al., 1985). The aim of this case-study was to compare the generally recognized gold-standard method for the evaluation of the aerobic capacity, i.e., the maximal lactate steady state test (MLSS) with different methods of evaluation of AnT in swimming. Methods: A female elite endurance swimmer (16 yr; 56 kg; 1.64 m) performed in different days a intermittent incremental protocols until voluntary exhaustion, with steps of 200m, increments of 0.05m/s between steps and 30s rest intervals, and two to four 30min sub-maximal tests at imposed pace to determine the MLSS, with a 2.5% difference between intensities (Pelarigo et al., 2011). In the incremental test, the blood lactate and the heart rate were analyzed during the 30s rest intervals and, in the MLSS, at the 10th and the 30th minute. MLSS was defined as the exercise intensity correspondent to the highest [La-] value that do not increase by no more than 1mmol/L between the 10th and 30th minute, and calculated as the average of the two [La-] values. The individual anaerobic threshold (IAnT) was calculated by the [La-] vs velocity curve modeling method (Machado et al., 2006) and the swimming velocity corresponding to 3.5 (3.5AnT) and 4mmol/L (4AnT) (Heck et al., 1985). Results: The values of MLSS (1.33 m/s, 1.80 mmol/L and 194 bpm) showed that the IAnT (1.30 m/s, 1.46 mmol/L and 186 bpm) slightly underestimate the gold standard outcomes, while the 3.5AnT (1.41 m/s and 201 bpm) and 4AnT (1.43 m/s and 203 bpm) overestimate the correspondent exercise intensity. Conclusions: Therefore, when compared the anaerobic threshold assessed through fixed [La-] values (3.5 and 4mmol) with the gold-standard method to evaluate the aerobic capacity (MLSS), the difference is higher than when IAnT is used. When MLSS is not possible to implement, the present case study results suggests that the IAnT will allow a more reliable prescription of exercise intensity for the evaluation of elite endurance athletes.